Role-play as a catalyst for justice awareness: a relational approach to nature-based solutions with secondary school students - Eugenia Castellazzi; Viola Hakkarainen; Christopher M. Raymond (Ecosystems and People)
Increasing attention to the concept of nature-based solutions (NBS) requests a reflection on the role of young people for just urban development. This study explores how upper secondary school students (age from 16 to 19) relationally learn about environmental justice issues through role-play. Ten workshops were conducted in May 2022, involving 197 students from two upper secondary schools in Helsinki, Finland. We used role-play as a learning activity to actively involve students in working with justice perceptions which emerged from discussions about the implementation of NBS in their school district. The findings are based on both participant observation and two surveys conducted before and after the activity. The study shows how the role-play positively impacted the students’ understanding of environmental justice issues related to NBS, complementing it with a higher recognition of different values for green spaces and trade-offs concerning their management. Finally, the role-play enabled students to explore new perceptions of recognition justice, expanding their sense of community to new cultures and non-human entities.